2019
DOI: 10.1108/ijmf-12-2017-0283
|View full text |Cite
|
Sign up to set email alerts
|

Board structure and financial distress in Brazilian firms

Abstract: Purpose The purpose of this paper is to investigate what board characteristics affect companies in periods of financial distress (FD) among non-financial Brazilian firms and examine which model best fits to predict FD. Design/methodology/approach The sample comprises data from 2010 to 2016 of the non-financial Brazilian firms listed on the Brazilian Stock Exchange. To measure this relationship, a conditional logistic regression is performed. Findings A U-shaped relationship between the size of the board of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
0
12
0
13
Order By: Relevance
“…Ukuran dewan direksi yang kecil sering terjadi kondisi kesulitan keuangan, karena memiliki tingkat risiko yang lebih tinggi (Candradewi & Rahyuda, 2021;Mariano et al, 2019). Ukuran dewan direksi juga membantu mencapai target daripada valuasi perusahaan, karena mempunyai kekuasaan dalam mengontrol pemegang saham (Freitas Cardoso et al, 2019).…”
Section: Ukuran Dewan Direksi Dan Kesulitan Keuanganunclassified
See 2 more Smart Citations
“…Ukuran dewan direksi yang kecil sering terjadi kondisi kesulitan keuangan, karena memiliki tingkat risiko yang lebih tinggi (Candradewi & Rahyuda, 2021;Mariano et al, 2019). Ukuran dewan direksi juga membantu mencapai target daripada valuasi perusahaan, karena mempunyai kekuasaan dalam mengontrol pemegang saham (Freitas Cardoso et al, 2019).…”
Section: Ukuran Dewan Direksi Dan Kesulitan Keuanganunclassified
“…Independensi dewan dapat membantu mengambil keputusan yang lebih objektif dan memimpin kinerja perusahaan ke arah yang lebih baik (Mohd Ali & Mohd Nasir, 2018). Peran dewan independen dalam perusahaan membantu memonitor para manajer untuk meningkatkan nilai perusahaan (Freitas Cardoso et al, 2019). Demikian juga dengan Khurshid et al (2018), mengatakan bahwa direksi independen meningkatkan kualitas pengambilan keputusan dan mengurangi risiko konflik antar kepentingan.…”
Section: Independensi Dewan Direksi Dan Kesulitan Keuanganunclassified
See 1 more Smart Citation
“…The first regulation is "Document No. 18", issued on 19 October, 2013, which prohibits state officials from holding any positions in enterprises [Freitas Cardoso, Peixoto, Barboza, 2019]. It influences independent academic directors indirectly since many of them work in state universities.…”
Section: Board Independencementioning
confidence: 99%
“…The corporate board structure can also be used to address agency problems (Manzaneque et al, 2016). Previous research found that the proportion of independent commissioners can reduce the possibility of financial distress because one of the board of commissioners' duty is to control the potential for opportunism made by management, hence this can reduce agency problems (Freitas Cardoso, Peixoto, & Barboza, 2019;Hui & Jing-jing, 2008;Li et al, 2020;Manzaneque et al, 2016;Salloum et al, 2013). However, Cinantya and Merkusiwati (2015) and Miglani et al (2015) found that the number of independent commissioners can actually increase the possibility of financial distress because often times, independent commissioners have a lack of independence, so the monitoring of the performance and behavior of company's management becomes weak.…”
Section: Introductionmentioning
confidence: 99%